The conceptualization of jihad in the Acehnese saga of Hikayat Prang Sabi - Herman Rusli; Mukhlis Mukhlis; Abu Bakar; Armia Armia (Universitas Syiah Kuala, 2022)
This study focuses on the conceptualization of jihad in the text of Hikayat Prang Sabi by Teungku Chik Pante Kulu. This study provides a constructive discourse of thought for readers in understanding jihad. This study narrates jihad as literally meaning ‘striving’ or ‘struggling’ in Arabic, such as in wars, and it also examines the conceptualization of jihad in Acehnese literary texts. The method used in this research is descriptive-qualitative. The data were analyzed through a literary hermeneutic approach so that the interpretation of the Hikayat Prang Sabi text can be considered a universal truth in the lives of the Acehnese and Muslim communities in the world regarding the concept of jihad. The results of the analysis show that the concept of jihad in the Hikayat Prang Sabi is divided into three: (1) jihad for religious reasons, (2) jihad to defend the homeland, and (3) jihad for peace. These three concepts form the conceptualization of jihad based on the relationship between humans and God, the relationship between humans and humans, and the relationship between humans and the universe. This confirms the linguistic concept of jihad in the perspective of Muslims, especially the people of Aceh, that jihad is not only about war and suicide but also an inspiration to call for truth and peace.